PROVISIONAL CHECKLIST OF GINGERS FROM TAMA ABU PF - Meekiong, Kalu; Aimi Syazana, Sedek; Nur Syauqina Syasya, Mohd Yusoff; Zinnirah, Shabdin; Mohd Isa, Miraadila (Forest Department Sarawak, 2019)
Zingiberaceae species are a diverse group of rhizomatous, aromatic perennial herbs with the centre of diversity in South-east Asia. The Zingiberaceae diversity in the Tama Abu Production Forest TAPF) documented in this paper is a result of the survey during the Heart of Borneo (HaB) Scientific Expedition 2017- A total of 44 species belonging to 12 genera and 2 tribes were collected and recorded. The tribe Alpinieae represented by 1 genera and 30 species whilst tribe Zingiberaea with 4 genera and 14 species. Amomum anomalum, Amomum dimorphum, Etlingen brevilabrum, Etlingera coccinea, Glabba atrosanguinea, Hornstedtia havilandii, Plagiastachys strobilifera and Zingiber sp- nov- are considered as common.